Sustainable value generation in the Chinese truck sector: role of a regenerative result-oriented product-service business model - Pallaro, Estelle (2018)
Challenges faced today in the truck industry indicate a need for transformation in truck manufacturers’ business logic. First, current business models are based on the sales of new vehicles so truck manufacturers fail to capture substantial financial benefits from servicing the installed base. Second, the truck market is prone to regional market cycles, which necessitates truck manufacturers to find solutions to stabilize their revenues. Moreover, environmental legislation and social pressures encourage truck manufacturers to look for solutions to preserve natural resources and enhance social welfare. To address these challenges, this study examines a regenerative result-oriented product-service (RROPS) business model, which combines a result-oriented product-service system and a closed-loop supply chain. By adopting a RROPS business model, truck manufacturers can earn regular sources of revenues, because demand for services is counter-cyclical, while improving their environmental and social performance. Hence, the goal of this study is to establish how to generate sustainable value for truck manufacturers.